Implications of the Women's Empowerment and Child Protection Service (DP3A) Program in Malang Regency - Setyowati, Eka (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
Violence experienced by women and children is still a common case in Indonesia. The Women's Empowerment and Child Protection Service (DP3A) of Malang Regency is an agency that has the task and authority to prevent violence against women and children. This journal will write about the implications of the Women's Empowerment and Child Protection Service (DP3A) Program of Malang Regency in efforts to prevent violence against women and children in the Malang Regency area in 2024. The theoretical study used is the role theory studied using descriptive qualitative analysis. The results of the study explain that the Women's Empowerment and Child Protection Service (DP3A) of Malang Regency has played an active, participatory role and there is also a passive role through programs that have been created. Although there are several obstacles in the implications of the programs being run, including due to budget limitations and limited human resources, DP3A always looks for the best solution